Revitalizing the Teacher's Role as Murabbi through Fazlur Rahman's Qur'anic Hermeneutics in Digital Pedagogy - Amir, Syuhud Syayadi; Fitrian, Zaglul; Afifullah, A; Maimun, M; Alrawashdeh, Khadeejeh (Universitas Muhammadiyah Surakarta, 2025)
The revitalization of the teacher's role as murabbi in the digital era is an urgent necessity to preserve the holistic and spiritual essence of Islamic education. The rapid advancement of digital technology has transformed learning interactions, often reducing them to transactional exchanges and diminishing the moral and spiritual bond between teachers and students. This study aims to explore how Fazlur Rahman's double-movement hermeneutic approach to Surah Āli 'Imrān (3:79) can offer a conceptual foundation for restoring the role of teachers as murabbi in the digital context. Using a qualitative library research method that analyzes both classical and contemporary tafsīr and studies on hermeneutics and Islamic pedagogy, the research follows three stages: historical analysis of the verse, extraction of moral values, and contextual application in digital education. The findings reveal that the ideal murabbi embodies intellectual mastery, moral integrity, and spiritual guidance rooted in rabbāniyyah values. The study concludes that integrating these values into digital pedagogy can strengthen ethical and spiritual dimensions in education. Theoretically, it contributes to the discourse on Islamic hermeneutics and digital pedagogy, while practically, it provides insights for teachers and institutions to implement rabbāniyyah-based education in digital learning environments.